Effectiveness of Green Tea Extract in Maintaining Viability of Avulsed Tooth Fibroblasts in Rats - Rahmawan, Dzanuar; Fharadiba, Alfinta Azzahra; Irawan, Rudi; Pertami, Sawitri Dwi Indah (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2026)
Tooth avulsion represents a severe traumatic dental injury in which a tooth is forcibly expelled from its alveolar socket, potentially resulting in significant damage to the surrounding periodontal structures. The success of replantation procedures is primarily determined by the condition and survivability of periodontal ligament (PDL) fibroblast cells. To maintain cellular integrity before replantation, the use of an appropriate storage medium is essential. Green tea (Camellia sinensis) is a herbal plant rich in flavonoid compounds that possess antioxidant and tissue-regenerative capabilities, particularly in stimulating fibroblast proliferation. A concentration of 70% green tea extract has been identified as the most beneficial for promoting wound recovery. This investigation sought to assess how effectively green tea extract could sustain fibroblast cell viability obtained from avulsed teeth of male Wistar rats. A total of thirty-six teeth harvested from male Wistar rats were allocated into one control group and two experimental groups, each subsequently subdivided based on immersion duration of 30 and 60 minutes. PDL-derived fibroblast cells were obtained through versene-trypsin isolation, followed by staining using 0.4% trypan blue solution and cell counting via hemocytometer under light microscopy. Results demonstrated that 30-minute immersion in 70% green tea extract yielded the highest fibroblast viability (90.35%; p = 0.004) relative to all other groups. Although both 70% and 100% concentrations successfully maintained fibroblast viability, the 70% concentration proved more effective across both observation time points.